2016
DOI: 10.3390/batteries2030027
|View full text |Cite
|
Sign up to set email alerts
|

Studies on MgNi-Based Metal Hydride Electrode with Aqueous Electrolytes Composed of Various Hydroxides

Abstract: Abstract:Compositions of MgNi-based amorphous-monocrystalline thin films produced by radio frequency (RF) sputtering with a varying composition target have been optimized. The composition Mg 52 Ni 39 Co 3 Mn 6 is identified to possess the highest initial discharge capacity of 640 mAh·g −1 with a 50 mA·g −1 discharge current density. Reproduction in bulk form of Mg 52 Ni 39 Co 3 Mn 6 alloy composition was prepared through a combination of melt spinning (MS) and mechanical alloying (MA), shows a sponge-like micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The AR3 MH alloy is very reactive to the KOH electrolyte due to the alloy's high content of Mg and the high porosity caused by the mechanical alloying preparation [12]. A rapid decay in the KOH electrolyte was previously reported [5,6,12]. Figure 2 shows an increase in initial discharge capacity and a decrease in capacity decay with the addition of Cs 2 CO 3 .…”
Section: Electrochemical Performances For Electrolytes With Cs 2 Co 3mentioning
confidence: 67%
See 2 more Smart Citations
“…The AR3 MH alloy is very reactive to the KOH electrolyte due to the alloy's high content of Mg and the high porosity caused by the mechanical alloying preparation [12]. A rapid decay in the KOH electrolyte was previously reported [5,6,12]. Figure 2 shows an increase in initial discharge capacity and a decrease in capacity decay with the addition of Cs 2 CO 3 .…”
Section: Electrochemical Performances For Electrolytes With Cs 2 Co 3mentioning
confidence: 67%
“…The effects of Cs 2 CO 3 on the AR3 alloy electrode performances are shown in Figure 2. The AR3 MH alloy is very reactive to the KOH electrolyte due to the alloy's high content of Mg and the high porosity caused by the mechanical alloying preparation [12]. A rapid decay in the KOH electrolyte was previously reported [5,6,12].…”
Section: Electrochemical Performances For Electrolytes With Cs 2 Co 3mentioning
confidence: 88%
See 1 more Smart Citation
“…In 2016, we reported that the reduction of the corrosion nature of the alkaline KOH electrolyte can be accomplished by selection of both adequate combination of alkaline species [22] and salt additives [23]. In this Special Issue, the effects of adding Cs 2 CO 3 salt in the electrolyte was further investigated, and a newly formed surface amorphous oxide was credited for the reduction of surface oxidation of the MgNi-based MH alloy [24].…”
Section: Electrolytementioning
confidence: 99%
“…The Ni segregation is more severe during slower rate discharges and needs to be controlled to sustain the initial capacity. Approaches for such segregation-prevention may include implantation of grain growth inhibitor [40], control of oxygen impurities [41], addition of elements with different solubilities among phases [42], addition of rare earth elements [43], addition of other transition metals with larger ionic radii, introduction of a pulse charge/discharge method to interrupt the formation of Ni(OH) 2 isolated grain, surface modification with surfactant to make it more difficult to precipitate into larger Ni(OH) 2 grains, a new combination of alkali [44] and salt [45] used in the electrolyte, and improvements in the co-precipitation process to evenly distribute the cation in the hydroxide. discussed in Section 3.1.…”
Section: Scanning Electron Microscopy/energy Dispersive Spectroscopy mentioning
confidence: 99%